2017
DOI: 10.1002/2017gl075395
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐Induced Melting in Collisions of Water Ice Nanograins: Strong Deformations and Prevention of Bouncing

Abstract: Collisions between ice grains are ubiquitous in the outer solar system. The mechanics of such collisions is traditionally described by the elastic contact theory of adhesive spheres. Here we use molecular dynamics simulations to study collisions between nanometer-sized amorphous water ice grains. We demonstrate that the collision-induced heating leads to grain melting in the interface of the colliding grains. The large lateral deformations and grain sticking induced considerably modify available macroscopic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…This shows that the role of the attractive forces between the two NPs is not well reproduced by JKR theory. A similar failure of JKR was noticed previously in the collision of silica NPs (Nietiadi et al 2017b), and even more so in the collision of ice NPs (Nietiadi et al 2017a).…”
Section: Contact Radiussupporting
confidence: 84%
See 1 more Smart Citation
“…This shows that the role of the attractive forces between the two NPs is not well reproduced by JKR theory. A similar failure of JKR was noticed previously in the collision of silica NPs (Nietiadi et al 2017b), and even more so in the collision of ice NPs (Nietiadi et al 2017a).…”
Section: Contact Radiussupporting
confidence: 84%
“…It has been shown that silica nanoparticles will stick during collisions at velocities that are not too high (Nietiadi et al 2017b), owing to their high surface energy; when the surface is passivated by H atoms, the bouncing velocity is reduced by a factor of almost an order of magnitude (Nietiadi et al 2020). Ice NPs, on the other hand, will stick at all collision velocities, since at higher velocities collision-induced melting lets them readily deform and prevents bouncing (Nietiadi et al 2017a). In an astrophysical context, NP sticking is relevant since it leads to mass agglomeration and thus dust growth (Dominik & Tielens 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This type of simulation is often used to study sticking and bouncing of nanoclusters, where melting and mixing of simple monoatomic substances have been observed. 15 However, to some surprise, our particles simply bounced of each other with no apparent mixing and indeed little effect on the particles' structure. This occurred even at much faster (supersonic) impact velocities.…”
Section: Resultsmentioning
confidence: 83%
“…The collisions were induced by augmenting the initial velocities of the atoms in the aspirin and meloxicam spheres with equal and opposite translational centre of mass (COM) velocities. This type of simulation is often used to study sticking and bouncing of nanoclusters, where melting and mixing of simple monoatomic substances have been observed 15. However, to some surprise, our particles simply bounced of each other with no apparent mixing and indeed little effect on the particles' structure.…”
Section: Resultsmentioning
confidence: 96%
“…v b is taken as the arithmetic mean of the highest sticking velocity and the lowest bouncing velocity; these two latter values are also taken to indicate the error of our computation in the plots. The simulations were performed using the open-source software LAMMPS [ 14 ], and the code is essentially the same as that used in our previous studies on collisions of silica [ 7 ] and water-ice particles [ 15 ].…”
Section: Methods/experimentalmentioning
confidence: 99%